Where are you now? an exploratory study on 'ghosting' as a method of terminating romantic relationships - Sales, Jaira Beatrice P. (College of Arts and Letters, University of the Philippines Diliman, 2019)
This qualitative study explore how 'ghosting' is used a method of terminating romantic relationships. Six heterosexual college students, those who have been 'ghodted' and have 'ghosted' narrated their experiences toward the said phenomenon through individual, semi structured and in-depth interviews. This aims to define 'ghosting' as a method of terminating romantic relationships, describe the experiences toward 'ghosting,' explore the motivations of 'ghosting,' discuss the effects of 'ghosting' to adolescents who have been 'ghosted' and coping mechanisms used by the adolescents, and discuss the impact of 'ghosting' in establishing new relationships. All the participants agreed the 'ghosting' is a method of terminating romantic relationship where an adolescent intentionally eliminates all means of communication to terminate the relationship. This is done through social media platforms and technological devices without informing the other adolescent, which eventually leads to dismissal of any face-to-face interaction. Adolescents who 'ghosted' experienced several motivations that led to the decision disengage with the partner using 'ghosting'. This, then, had an effect on those who had been 'ghosted'. With that, different coping strategies were employed by the adolescents who had been 'ghosted' to resolve the effects gained form the 'ghosting' experiences. Lastly, negative impacts in establishing new romantic relationships to those who had been 'ghosted' were also analyzed.The study highlighted the change in interpersonal relationships as influenced by technology and digital age. It explained how 'ghosting' is now indeed, a new alternative method for an adolescent to use when terminating romantic relationships.